Novel HLA-A2-restricted human metapneumovirus epitopes reduce viral titers in mice and are recognized by human T cells. Issue 24 (23rd May 2016) - Hastings, Andrew K.; Gilchuk, Pavlo; Joyce, Sebastian; Williams, John V.
Abstract: Human metapneumovirus (HMPV) is a major cause of morbidity and mortality from acute lower respiratory tract illness, with most individuals seropositive by age five. Despite the presence of neutralizing antibodies, secondary infections are common and can be severe in young, elderly, and immunocompromised persons. Preclinical vaccine studies for HMPV have suggested a need for a balanced antibody and T cell immune response to enhance protection and avoid lung immunopathology. We infected transgenic mice expressing human HLA-A*0201 with HMPV and used ELISPOT to screen overlapping and predicted epitope peptides. We identified six novel HLA-A2 restricted CD8 + T cell (TCD8 ) epitopes, with M39–47 (M39) immunodominant. Tetramer staining detected M39-specific TCD8 in lungs and spleen of HMPV-immune mice. Immunization with adjuvant-formulated M39 peptide reduced lung virus titers upon challenge. Finally, we show that TCD8 from HLA-A*0201 positive humans recognize M39 by IFNγ ELISPOT and tetramer staining. These results will facilitate HMPV vaccine development and human studies.